Bacterial community changes with granule size in cryoconite and their susceptibility to exogenous nutrients on NW Greenland glaciers. Issue 7 (27th May 2019) - Uetake, Jun; Nagatsuka, Naoko; Onuma, Yukihiko; Takeuchi, Nozomu; Motoyama, Hideaki; Aoki, Teruo
ABSTRACT: Cryoconite granules are dark-colored biological aggregates on glaciers. Bacterial community varies with granule size, however, community change in space and their susceptibility to environmental factors has not been described yet. Therefore, we focused on bacterial community from four different granule sizes (30–249 μm, 250–750 μm, 750–1599 μm, more than 1600 μm diameter) in 10 glaciers in northwestern Greenland and their susceptibility to exogenous nutrients in cryoconite hole. A filamentous cyanobacterium Phormidesmis priestleyi, which has been frequently reported from glaciers in Arctic was abundant (10%–26%) across any size of granules on most of glaciers. Bacterial community across glaciers became similar with size increase, and whence smallest size fractions contain more unique genera in each glacier. Multivariate analysis revealed that effect of nutrients to beta diversity is larger in smaller granules (30–249 μm and 250–750 μm diameter), suggesting that bacterial susceptibility to nutrients changes with growth of granule (i.e. P. priestleyi was affected by nitrate in early growth stage). Abstract : In ten northwestern Greenland glaciers the bacterial community composition was different in four different grain sizes of cryoconite. Their susceptibility to exogenous nutrients in the cryoconite holes also changed.